SIFAT KIMIA TANAH DAN PERTUMBUHAN BIBIT SENGON (Paraserianthes falcataria (L.) Nielsen) YANG DIBERI KOMPOS DI TANAH SUB SOIL TAMBANG NIKEL - Lies Indriyani; Hasbullah Syaf; Muhammad Albar Pattah (Universitas Haluoleo, 2015)
The purpose of this research was to know the effect of giving compost in sub soil (over burden) nickel mine toward chemical properties of soil and growth of sengon crop seed in an effort for introduce initial condition of the growing environment for sengon crop, so that earned seed for support revegetation activity of land ex minning. The research was arranged in Randomized Block Design (RBD) with single factor scheme for 7 treatment degree, that is A0 (without compost), A1 (125 g compost polybag-1), A2 (250 g compost polybag-1), A3 (375 g compost polybag-1), A4 (500 g compost polybag-1), A5 (625 g compost polybag-1) and A6 (750 g compost polybag-1). The treatment reapet for 3 times so that has 21 unit tried. Every experiment unit from 9 crop so that all over has 189 crop. Variable with observed are chemical properties of soil (pH, cation exchange capacity (CEC), N-total, available P and available K) and sengon crop growing (increase high crop (cm), total leaf stalk (stalk), stem diameter (cm), ratio root tip of a leaf and index quality of seed). The research shown that compost fertilizer giving toward chemical properties of sub soil (over burden) nickel mine raising of value for soil pH, CEC, N-total, available P and available K. However, compost giving toward sengon growth only show effect more real the increase high crop in age 45 hst. Key Word : Chemical properties of soil, compost, growth of sengon crop.